(7x+33)=(9x+7)

Simple and best practice solution for (7x+33)=(9x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x+33)=(9x+7) equation:


Simplifying
(7x + 33) = (9x + 7)

Reorder the terms:
(33 + 7x) = (9x + 7)

Remove parenthesis around (33 + 7x)
33 + 7x = (9x + 7)

Reorder the terms:
33 + 7x = (7 + 9x)

Remove parenthesis around (7 + 9x)
33 + 7x = 7 + 9x

Solving
33 + 7x = 7 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
33 + 7x + -9x = 7 + 9x + -9x

Combine like terms: 7x + -9x = -2x
33 + -2x = 7 + 9x + -9x

Combine like terms: 9x + -9x = 0
33 + -2x = 7 + 0
33 + -2x = 7

Add '-33' to each side of the equation.
33 + -33 + -2x = 7 + -33

Combine like terms: 33 + -33 = 0
0 + -2x = 7 + -33
-2x = 7 + -33

Combine like terms: 7 + -33 = -26
-2x = -26

Divide each side by '-2'.
x = 13

Simplifying
x = 13

See similar equations:

| 9=2r-5 | | 2x-29=93 | | 23x+5x=2x | | -4(-2x+2)+8x=-(5x+7) | | X-47=12 | | X+3=3+2(2+3x)-5x | | x+x-30=180 | | 6(6x-11)=54x | | b=60+(15+7) | | -5d=20 | | x-30=180 | | (8x-4)+(10x+6)= | | 5x-3=-3x-1 | | (X-7)+12=20 | | 7a-18=-3(-3+3)+7a | | x+15=4x-36 | | -40=b-51 | | H=7+27t-16t^2 | | x*15=4x-36 | | 6(x-11)=54x | | -9r-18r-3r=-12 | | 28=4s+r-s | | 4(3x+3)=3(5x+0.5) | | 1204.2528=2*3.14*6.8*6.8+2*3.14*6.8*h | | 4a-3a=a | | 0=x^2+2x+420 | | 4p+2=-3p+5p | | 4x+0.5= | | h=-2t^2+8t | | h=-2t^2+8tZ | | 17.18=3g+3.89 | | 11-3a=1-a |

Equations solver categories